ARABIC-THE UNIQUE BLEMISH HADITHS IN AL-MU'JAM AL-AWSAT AND THEIR APPENDAGES - Evi Hanafi; Masood Ahmed (دی اسکالر)
Al-Mu'jam Al-Awasat by Imam Sulaiman bin Ahmad Al-Tabarani consists of hadiths with the chain of transmission. Also, Imam Al- Tabarani had passed comments after a large number of the hadiths that there is individuality by the specific narrator from his teacher (Sheikh). These comments are regarding "Elal al-Hadith" that when a narrator individually narrated the hadith from his teacher so, it is considered a weakness in the hadith narrated by this chain of transmission. Although, the comments regarding this individuality are the difficult part of hadith's sciences, and only the specialist "Muhaddith" can do it. The individuality of a trustworthy narrator does not make any weakness in his narration, but the unique narration of an unreliable narrator is rejected among the scholars of hadith. It is also known in the hadith's sciences that the appendage (Mutaba'a) gives strength to and raises the level of any hadith in authenticity criteria and the status of a weak hadith can be raised to the rank of the good by means of another chain of transmission.